Bone Density in Post-Pubertal Adolescent Survivors of Childhood Brain Tumors - Cohen, Laurie E. (2011)
BACKGROUND: Childhood cancer survivors are at high risk for reduced bone mineral density (BMD). Our objective was to determine whether post-pubertal adolescent survivors of brain tumors, whose tumor or treatments placed them at risk for pituitary hormone deficiencies, have low BMD near time of peak bone mass accrual, and to assess risk factors for decreased BMD. PROCEDURE: Chart review of 36 post-pubertal adolescents with history of tumor or radiation therapy (RT) of the hypothalamic-pituitary area who had undergone BMD screening via dual-energy x-ray absorptiometry (DXA). RESULTS: Age at DXA was 16.9 ±1.9 years (mean ± SD). Time since diagnosis was 8.5 ±3.6 years. Median BMD Z-scores were −0.95 (range −2.7 to 1.7) at the femoral neck, −1.20 (−3.6 to 1.8) at the hip, and −0.90 (−3.7 to 1.8) at the spine. Bone mineral apparent density (BMAD) Z-scores were −0.23 (−2.7 to 1.9) at the femoral neck and −0.45 (−3.0 to 2.3) at the spine. Those with history of ≥1 fracture had lower BMD Z-scores of the femoral neck, total hip and spine (P<0.05). Those with treated GH deficiency had a higher BMD Z-score at the femoral neck, total hip and spine (P<0.05) than those not treated. There was no difference in BMD with respect to treatment with chemotherapy, cranial or spinal RT, or hypogonadism. Spontaneous menarche and regular periods did not correlate with BMD. CONCLUSIONS: In post-pubertal adolescent survivors of childhood brain tumors, fracture history and untreated GH deficiency are risk factors for decreased BMD.